Measurement of the mass of the top quark in decays with a J/? meson in pp collisions at 8 TeV - The, C. M. S. collaboration; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (My University, 2016)
A first measurement of the top quark mass in the decay channel t ? (W ? ??) (b ? J/? + X ? ?+?? + X) is presented. The analysis uses events selected from the proton-proton collisions recorded by the CMS detector at the LHC at a center-of-mass energy of 8 TeV. The data correspond to an integrated luminosity of 19.7 fb?1, with 666 t t ¯ and single top quark candidate events containing a reconstructed J/? candidate decaying into an oppositely-charged muon pair. The mass of the (J/? + ?) system, where ? is an electron or a muon from W boson decay, is used to extract a top quark mass of 173.5 ± 3.0 (stat) ± 0.9 (syst) GeV. © 2016, The Author(s).
Citation: The, C. M. S. c., Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., . . . Woods, N. (2016). Measurement of the mass of the top quark in decays with a J/? meson in pp collisions at 8 TeV. Journal of High Energy Physics, 2016(12). doi:10.1007/JHEP12(2016)123
Keywords: Hadron-Hadron Scattering (Experiments); Top Physics